Ethiopia's agricultural transformation: agribusiness' contribution to reducing youth unemployment - Assfaw Wossen, Tesfamicheal; Ayele, Seife (Institute of Development Studies, 2018)
This article explores empirical evidence on the relationship between agricultural transformation, ownership structure of agribusinesses, and employment creation in Ethiopia. It draws on secondary data to present evidence of Ethiopia’s agricultural transformation, employment trends, and the agribusiness sector’s contribution to employment generation. The country’s agricultural sector has shown signs of transformation in the form of both labour movement to the more productive manufacturing and services sectors, and productivity growth through the commercialisation and creation of agribusinesses. The findings suggest that the growing number of agribusinesses are generating more jobs for youth but also reveal a number of challenges to overcome, such as skills gaps, low pay in the private sector, and inflexible land ownership and transfer processes. The study suggests targeted policy reforms to incentivise efficient and competitive private agribusinesses, and to address agribusiness-related constraints, skills and wage gaps, as well as land ownership and rental market constraints.